The role of Islamic political parties in an Islamic state - an analysis of Jamaat-e-Islami - Usman Ghani, Syed Mohamed; Ushama, Thameem (IIUM Press, 2022)
The Islamic parties in Pakistan are a formidable force to be reckoned with and are regarded as one of the elite groups that impact political decisions and processes in Pakistan. They have incredible street power, albeit they did not do well in Pakistan‘s elections over the years. This article examines their political influence, which is disproportionate to their electoral support. They carve out a position among many elite groups, such as the military, bureaucratic, Punjabi, and business elite, who control Pakistan‘s political system and decision-making. Through their ties with organisations, they not only contributed to Jammu and Kashmir issues and exercised influence during the Afghan struggle but also continue to play a role in politics today. They have a significant influence on the politics of Pakistan. The Jamaat-e-Islami (JI), the Jamiat-ul-Ulema-i-Islam (JUI), and the Jamiat-ul-Ulema-i-Pakistan (JUP) could not get more than six seats altogether (combined) within the National Assembly. These parties are at the forefront on issues like establishing the Sharīᶜah Courts and legislation on matters like ushr, zakah, blasphemy, etc. Qualitative content analysis has been employed in analysing issues regarding the participation of the political parties in Pakistan.